Correction: Two Independent Mutations in ADAMTS17 Are Associated with Primary Open Angle Glaucoma in the Basset Hound and Basset Fauve de Bretagne Breeds of Dog. - James A C Oliver (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0140436.].